The impact of demographics on future blood supply and demand in Iceland - Guðlaug Jökulsdóttir 1987- (2013)
The focus of this research is in the area of population-based studies on demographic influences regarding blood supply and demand. Such a study is important in order to support studies in this field and highlight the impact of demographic changes on future blood supply and demand. The research approach adopted in this dissertation includes the identification of the problem of the reduction of the eligible donor population with a concomitant increase of patients requiring blood transfusions, the evaluation of a forecast model relevant to the problem and exploration of similar studies. The research methods consisted of a wide review of relevant literature on demographic changes, coupled with the collection and analysis of empirical data. The latter is based on data from the Icelandic Blood Bank and the Bureau of Statistics in Iceland, using a population-based cross-sectional research. The findings from this study provide evidence that demographic changes will affect both supply and demand of blood products in Iceland in the future. The main conclusions drawn from this study are that shortage of blood components is real and needs to be addressed. This dissertation recommends that the Icelandic Blood Bank further informs the youth about the importance of blood donations and how the process of donating blood works in order to increase the amount of blood donors in younger age groups. By increasing the number of younger blood donors, the shortage of blood supply will decrease. Primarily it is thus recommended that the Icelandic Blood Bank places emphasis on increasing the amount of female donors with the aim of equalizing male and female blood donors in Iceland. Keywords: demographics, blood supply, blood demand, Iceland, forecast. Áhersla þessa rannsóknar er á sviði íbúa-miðaðra rannsókna um lýðfræðileg áhrif varðandi framboð og eftirspurn blóðgjafa. Slík rannsókn er mikilvæg í því skyni að styðja við aðrar rannsóknir á þessu sviði og undirstrika áhrif lýðfræðilegra breytinga á framboð og eftirspurn blóðgjafa í ...